Délivrance, danger et scandale chez Camille Laurens et Chantal Chawaf. Issue 1 (1st January 2018) - Schwerdtner, Karin
ABSTRACT: This paper examines the risks involved in creating life and literature, as represented in work by Chantal Chawaf and Camille Laurens. Focusing on Chawaf's  Délivrance brisée  and on Laurens'  Philippe  as well as on the "scandals" surrounding their publication,  and drawing insight from interviews conducted with these authors, I address briefly how various "dangers" impact the processes of birth and (literary) creation.